Reduced-order methodology for prediction of loads generated by a flexible flapping wing. Issue 1 (March 2018) - Tran, Jason; Gao, Haotian; Sirohi, Jayant; Wei, Mingjun
This paper describes a methodology to predict the loads generated by a flexible flapping wing. The three-dimensional, whole field wing deformation was first measured using a non-contact optical technique. The measured deformation and motion were then input to a reduced-order model of the flapping wing to calculate the loads generated. Experiments were performed on a thin rectangular plate of 100 mm wing length flapping in air at a frequency of 15 Hz and stroke amplitude of 40°. The wing deformation as well as wing root loads were measured and showed good agreement with previously published data. A direct numerical simulation of the Navier–Stokes equation with exactly the same configuration, but at lower Reynolds number, provided full-field dataset for the development of data-driven reduced-order models. A modified proper orthogonal decomposition-Galerkin method, which includes extra terms to represent moving boundaries, was applied for reduced-order model development. It was found that the reduced-order model with only eight proper orthogonal decomposition modes was sufficient to show good correlation of loads with direct numerical simulations and experimentally measured trends.